QUALITY OF LIFE FOR WORKERS IN THE SÃO PATRÍCIO VALLEY (CIPEEX, 2026)
Introduction: Work plays a central role in human life, influencing aspirations and lifestyle and serving as a source of meaning. Well-being at work is directly related to Quality of Life at Work (QLW). Objective: To assess the quality of life of workers in the São Patrício Valley, in Goiás, considering the four domains: physical, psychological, social relations, and environment proposed by the World Health Organization Quality of Life (WHOQOL-BREF) questionnaire. Method: This is a quantitative, cross-sectional, descriptive study. Workers over 18 years of age who consented to participate in the study were included. Data collection was performed using a digital questionnaire administered in person. Quality of life was assessed using the WHOQOL-BREF, validated in Brazil. Results: A total of 804 workers participated, 63.7% of whom were women and 36.3% men. The medians for quality of life according to domain were: physical 71.4; psychological 66.7; social 75; and environmental 62.5. The overall score was 67.2. The psychological and environmental domains had the lowest perceptions of quality of life. Female gender was associated with a higher risk of low QoL perception in the physical (PR 1.33; 95% CI, 1.19-1.55), psychological (PR 1.45; 95% CI 1.24-1.69) and total score (PR 1.50; 95% CI 1.27-1.76). Conclusion: The lowest perceptions of quality of life occurred in the psychological and environmental domains, especially among women. These findings reinforce the need for interventions targeting these factors to improve the quality of life of this population.
Keywords: Quality of life; Workers; Quality of life for workers